ESET histone methyltransferase regulates osteoblastic differentiation of mesenchymal stem cells during postnatal bone development - Lawson, Kevin A. (2013)
To investigate the effects of histone methyltransferase ESET (also known as SETDB1) on bone metabolism, we analyzed osteoblasts and osteoclasts in ESET knockout animals, and performed osteogenesis assays using ESET-null mesenchymal stem cells. We found that ESET deletion severely impairs osteoblast differentiation but has no effect on osteoclastogenesis, that co-transfection of ESET represses Runx2-mediated luciferase reporter while siRNA knockdown of ESET activates the luciferase reporter in mesenchymal cells, and that ESET is required for postnatal expression of Indian hedgehog protein in the growth plate. As the bone phenotype in ESET-null mice is 100% penetrant, these results support ESET as a critical regulator of osteoblast differentiation during bone development.